A System for Accurate Deployment of Unconstrained Triple-Fenestrated Aortic Arch Endografts. (December 2022) - Joseph, George; Thomson, Viji Samuel; Thankachen, Roy; Kota, Albert; George, Oommen K.; Jose, John; Joseph, Elizabeth; Sahajanandan, Raj
Purpose: To achieve accurate rotational orientation and the axial position of unconstrained triple-fenestrated physician-modified endografts upon deployment in the aortic arch during total arch thoracic endovascular aortic repair (TA-TEVAR). Materials and Methods: Following a detailed study of reconstructed computerized tomography angiography images of patients' arch anatomy, customized, sealable fenestrations with radio-opaque margins are created onsite on Valiant Captivia (Medtronic) endografts, transposing the arch branch ostial anatomic interrelationship onto the endograft precisely. Radio-opaque figure-of-8 markers, indicating the 12 o'clock (superior) position, are attached to the endograft on the surface and brought up to the surface under the endograft cover during resheathing. Resheathing without any twist in the endograft is achieved by lining up the welds in each endograft stent segment in a straight line. The fluoroscopic working view for arch endograft delivery and deployment is the left anterior oblique view that is orthogonal to the plane of the arch, which, in turn, is the right anterior oblique view in which parts of a stiff indwelling guidewire in the ascending and descending aorta precisely overlap. During introduction in the working view, the endograft delivery system is rotated in the descending thoracic aorta so that the 12 o'clock figure-of-8 markers are viewed on the edge and situated at the outer aortic curvature; continued advancement into the arch without any further rotation will ensure superior orientation of the figure-of-8 markers and, consequently, correct endograft rotational orientation. Proper axial endograft positioning requires locating the left common carotid artery (LCCA) fenestration just proximal to a taut externalized LCCA-femoral guidewire loop marking the posterior limit of the LCCA ostium. After endograft deployment during rapid cardiac pacing, the target arch branches are cannulated through their respective fenestrations using hydrophilic 0.035-inch guidewires that are externalized via distal sheaths to create femoral-arch branch (through-and-through) loops over which covered fenestrated stents are introduced and deployed. Results: This technique was used successfully in 31 consecutive patients undergoing TA-TEVAR; systemic blood pressure was obtained in all arch branches immediately after endograft deployment, indicating adequate blood flow. All arch branches were successfully cannulated and stented. Conclusion: This system enables accurate deployment of unconstrained triple-fenestrated arch endografts simply and reliably during TA-TEVAR.